RESPONS MAHASISWA TERHADAP PENGGUNAAN MODUL “SEDEKAH, HIBAH, DAN HADIAH” PADA MATA KULIAH PENDIDIKAN AGAMA ISLAM DI AKADEMI FARMASI AL-FATAH BENGKULU - Nanik Nanik (Universitas Islam Negeri Fatmawati Sukarno, 2018)
The formulation of the problem in this study is how students respond to learning Islamic Education (PAI) courses using the “Alms, Grants and Gifts” module at the Bengkulu Al-Fatah Pharmacy Academy. This research is in- cluded in quantitative descriptive research. The population in this study were all third semester students at the Beng- kulu Al-Fatah Pharmacy Academy, while the research sample used was third semester B1 students at the Al-Fatah Pharmacy Academy Bengkulu Academic Year 2016-2017. The instruments used in this study were the student response questionnaire and the module “Alms, Grants and Gifts”. The technique of collecting data using questionnaires and test sheets. Based on the research that has been done, the results show that : The average percentage score of all students is82.86764706% and is classified as very high criteria. It can be concluded that the 3rd grade B1 Semester 3-2017 Academic Year at the Al-Fatah Pharmacy Academy gave a positive response to the learning of Islamic Education courses using the “Alms, Grants, and Gifts” module